Hubungan Jumlah Asupan Natrium dengan Kejadian Hipertensi pada Penderita Usia 45-59 Tahun di Kelurahan Sungai Harapan Wilayah Kerja Puskesmas Sekupang Kota Batam Tahun 2023 - Irma Suryani; Nelli Roza; Haqqelni Nur Rosyidah (Jurnal Kesehatan Amanah, 2024)
Hypertension is the most commonly experienced health problem that is often referred to as a silent killer because it is often without complaints. One of the factors causing hypertension is sodium intake. The purpose of this study was to determine the relationship between sodium intake and the incidence of hypertension at the age of 45-59 years in Sungai Harapan Village, Batam City. The research method used was a cross sectional design with a total sample of 96 people. The results showed that most respondents had high sodium intake as many as 57 people (59.4%) and most respondents experienced hypertension as many as 60 people (62.5%). Based on statistical analysis using the chi-square statistical test with a confidence level of α 0.05, the p value of 0.000 <0.05 was obtained. Thus, there is a relationship between sodium intake and the incidence of hypertension at the age of 45-59 years in Sungai Harapan Village, Sekupang Health Center Working Area, Batam City.